Prevalence of refractive error in children- hospital based study in Lucknow - Sharma, Pratik; Ali, Jamshed; Kumari, Ragni; Akhtar, Ramlah; Gupta, Sunil; Sharma, Amisha (International Journal of Research in Medical Sciences, 2022)
Background: Refractive error is defined as a status of refraction. They happen when the shape of your eye keeps light from focusing correctly on your retina (a light-sensitive layer of tissue in the back of your eye). Refractive errors are the most common type of vision problem but many don’t know that they could be seeing well. Methods: This study was a cross sectional hospital-based study of 197 children carried out in ophthalmology department of Era Medical College, Lucknow. The study of population comprised of all the children in 5-20 years’ (78 male 119 female) age group in the rural area. In this study compressive examination prevalence of myopia and hypermetropia. The assess refractive error among study with ‘hine retinoscopy’. Myopia considered grater or equal -0.50 and hyperopia is grater and equal +0.50. Results: The crossed section hospital-based study 197 children examined 78 male and 119 female. The uncorrected ametropia in children was 82.2%. The highly prevalence of myopia 46%, hypermetropia 5%, astigmatism 31%. The most highly significant refractive error 16-20 year of age. Conclusions: The prevalence of ametropia is fined among children in hospital visit. Need for regular routine cheek up proper ophthalmic assessment examination of eye and full proper diet and distance with digital gadget.